“Bicentennial Generation” in Cristina Fernandez’ speeches - Flax, Rocío (Lenguas Modernas, 2018)
In this paper we analyze the use, during 2010 and 2011, of the phrases “Bicentennial Generation” and “Bicentennial Youth” in public speeches by the ex President Cristina Fernandez de Kirchner. We believe that the reference of the phrase develops a series of changes: first, “Bicentennial Generation” refers to the generation of Cristina Fernandez and, after a coexistence of both meanings, it refers to today’s youth. In order to understand the change, we will observe the social action in which the text is involved and the different assessments and modalizations that are ascribed to the phrase “Bicentennial Generation”. We will take analysis tools from Socio-Discursive Interactionism.